Answer:
t = 6 km/hour
And, J would be 4 km per hour
Step-by-step explanation:
Let us assume the speed of Tom be T
And, the Speed of Jim be J
Given that
T - J = 2 km /hr ...........(i)
After 3 hours distance between them = 30 km
As they are walking in the opposite direction
Thus,
Net speed =T + J
L ÷ (T+J) = 3
30 ÷ (T+J) = 3
T +J =10 ..............(2)
After solving these two equations
2T = 12
t = 6 km/hour
And, J would be 4 km per hour
Answer:
and yeah ikr I don't understand why
Answer:
Step-by-step explanation:
Integer roots:
a = 6 n + 1, b = 7, c = -3 n^2 - n, n element Z
a = 6 n + 5, b = 7, c = -3 n^2 - 5 n - 2, n element Z
Derivative:
d/da(1/7 (a^2 + 12 c) b - 1) = (2 a b)/7
Indefinite integral:
integral(-1 + 1/7 b (a^2 + 12 c)) da = (a^3 b)/21 + (12 a b c)/7 - a + constant
Related Queries:
Answer:
hope this helps you in some way